'And Making Death a Victory': Scepticism and Personal Conflict in Childe Harold's Pilgrimage I–II and 'Prometheus'. Issue 1 (June 2020) - Marchionni, Francesco
Abstract : This article explores Byron's interest in the hybris / nemesis dichotomy of the Promethean poetic trope in his oeuvre, based on his reading of Aeschylus's Prometheus Bound . Drawing on theories of writing by Nietzsche and Derrida, the article addresses the ways in which the Promethean acts as a supplement of Byron's poetic selfhood, constructing a discourse of scepticism about poetic truth, and the tragedy of Byron the poet conflicted between creation and destruction. The reading of the past/present dichotomy in Childe Harold's Pilgrimage I–II highlights an early Byronic awareness of the tragic force inhabiting poetry, defacing the illusion of lyrical symbolism. The analysis of 'Prometheus' invites a further discussion of Byronic scepticism in light of his meditations on mourning, death and posterity, as well as addressing the ways in which the dramatic pattern of the poem resembles the fragmentation of poetic thought between composition and mental performance.